1996
DOI: 10.1080/1363682960480406
|View full text |Cite
|
Sign up to set email alerts
|

Clerical‐Administrative Workers’ Conceptions of Competence in their Jobs

Abstract: The growing number of government-sourced reports on improving economic performance of the nation through a carefully-orchestrated National Training Reform Agenda have used the concept of competence as a central plank in their philosophy. All of these reports draw on a rationalistic perspective of competence that is built around designated behavioural outcomes. These outcomes are established in a dualistic way. An alternative approach is to use a humanistic approach to competence in which the concept of compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…These findings have also been confirmed in more recent empirical studies on competence (e.g. Blomberg, 2004; Chen and Partington, 2004; Dall'Alba, 2004; Gerber and Velde, 1996, 1997; Partington et al., 2005; Sandberg, 2001a; Stålsby‐Lundborg et al., 1999).…”
supporting
confidence: 66%
“…These findings have also been confirmed in more recent empirical studies on competence (e.g. Blomberg, 2004; Chen and Partington, 2004; Dall'Alba, 2004; Gerber and Velde, 1996, 1997; Partington et al., 2005; Sandberg, 2001a; Stålsby‐Lundborg et al., 1999).…”
supporting
confidence: 66%
“…Such a perspective of competence does not appear well researched in the literature arising from the implications of the National Training Reform Agenda (for example , Finn, 1991;Masters, 1992;Mayer, 1992;Thomson, 1993). Gerber & Velde (1996) adopted the intentional approach to exploring competence with the same population as in this study. The findings demonstrated that competence for clerical-administrative workers was a multifaceted and holistic concept.…”
Section: A Model For Reporting Trainee Competencementioning
confidence: 99%
“…Pode-se pressupor que essa trajetória tenha ocorrido graças à fronteira entre a educação profissional e de nível superior com a expectativa sobre o desenvolvimento de competências profissionais e gerenciais das organizações, considerando as implicações nos aspectos práticos de treinamento para formação destas competências. Os trabalhos de Sandberg e Dall'Alba (1996), Velde e Gerber (1996Gerber ( , 1997 De forma consistente com essa vertente, seguiram-se os estudos de Partington (2002Partington ( , 2004Partington ( , 2006Partington ( , 2008Partington ( , 2009 Sandberg (2000). Foram identificadas 3 diferentes concepções básicas de trabalho de gestão de projetos, com diferentes atributos de experiência e realização do trabalho, refletindo-se em um arranjo hierarquizado de distintas formas de competências.…”
Section: Aplicação Do Método Em Estudos Organizacionaisunclassified